Internal users' self assessment of Malaysia's e-government flagship applications in lead implementation agencies - Mohamed, Norshidah (ICT Research and Development Programme, INTAN, Bukit Kiara, 2008)
This article presents the results of internal end-users' self assessment on Mlaysia's six e-Government flagship applications. e-Services, e-Procurement, Generic Office Environment (GOE), Human Resource Management Information System (HRMIS), Project Monitorng System (PMS) and Electronic Labor Exchange (ELX) were the six flagship applications assessed. The study adopted a cross-sectional survey research approach. Because e-government projects are still on-going, surrogate measures from the information systems success literature were used. A total of 437 questionnaires were distributed to non-clerical staff at seven lead implementation agencies namely the Road Transport Department (RTD), Treasury, the Malaysian Administration Modernisation and Management Planning Unit (MAMPU), Public Service Department (PSD), Ministry of Human Resources (MOHR), the Implementation Coordination Unit (ICU) and the Ministry of Health (MOH), The Usable response rate was 29.7%. While there was evidence from internal users' perspective to suggest that the e-Government applications were generally successful in lead implementation agencies, there is variability in perceived relative systems success for the flagship applications.